Voces y registros anticanónicos de la posguerra - Méndez de Penedo, Lucrecia (2017)
One of postwar Guatemalan literary movements is the so called Generation X, positioned critically as an alternative to sanctioned culture. These young artists and writers, in constant mobility, refused the structures that emarginated them. Positioned in a peripheral postmodernity, their point of reference was globalization, as a radical change of culture. They disregarded historical memory, authorized canon, conventional moral codes, the great narratives and dived deeply -and sometimes dangerously- into their private sphere, without utopian horizons. As a reaction to big or small editorials that overlooked them, they generated their own means of marketing their editorial products.